Compression with 23 mmHg or 35 mmHg stockings after saphenous catheter foam sclerotherapy and phlebectomy of varicose veins: A randomized controlled study. (March 2019) - Cavezzi, Attilio; Mosti, Giovanni; Colucci, Roberto; Quinzi, Valentina; Bastiani, Luca; Urso, Simone U
Objectives: To compare two different medical compression stockings after varicose vein treatment. Patients and methods: A randomized single-blind controlled study on two compression regimes after saphenous catheter foam sclerotherapy + phlebectomy was performed. After pads and 5 mmHg contention sock, 23 mmHg (group A, Struva 23®) or 35 mmHg (group B, Struva 35®) medical compression stocking was applied 24 h/day for seven days; subsequently 21–23 mmHg medical compression stocking in daytime. Symptoms, compliance, skin findings, and bioimpedance spectroscopy parameters were assessed. Results: A total of 94 patients (48 and 49 limbs in groups A and B, respectively) were enrolled. Three (T3) and seven (T7) days post-operatively, most symptoms were significantly milder in group B, especially pain and heaviness at T7 and at day 40 (T40). Ambulation, medical compression stocking stability/tolerability and skin healing were significantly better in group B, with p = 0.046, 0.021/0.060, and 0.010, respectively, at T7. Bioimpedance parameters increased at T7 and decreased at T40 in both groups; leg reactance and limb L-Dex improved in group B at T7 and T40, respectively (p = 0.039 and 0.012). Conclusions: Compression with 23 and 35 mmHg medical compression stocking after catheter foam sclerotherapy + phlebectomy was effective and well tolerated at immediate/short term. Compression with 35 mmHg medical compression stocking provided less adverse post-operative symptoms and better tissue healing. Bioimpedance results confirmed a slightly better edema improvement with 35 mmHg medical compression stocking.